Design of Shipping Lanes at Tanjung Ringgit Port Palopo City (International Journal of Metacentre, 2022)
One of the things that should not be left behind in the port development process is the availability of shipping lanes. The shipping lane is used to direct ships that will leave/enter the harbor pool. The shipping lane must have sufficient depth and width or in accordance with the draft of the ship so that it can be passed by ships that will use the port. This study aims to determine the characteristics of the shipping lanes in accordance with the needs of the ship and determine the location of the appropriate and efficient shipping lanes at Tanjung Ringgit Port, Palopo City. The method used to design the shipping lanes of Tanjung Ringgit Port, Palopo City, is by observation/survey, interview, and document study. The results of this study indicate that there is a navigational hazard, namely seaweed ponds for local residents, therefore the addition of Sailing Navigation Assistance Facilities in the form of 3 units of Red Flare Buoys. The depth at the entrance of the Tanjung Ringgit Port, Palopo City, starts from 9 meters – 23 meters with a channel length of 6,074 meters and a channel width of 300 meters so that a route system for the inlet and exit routes is made with a 2-way route system. Based on these results, the size of the ship with a DWT of 8000 tons, a maximum draft of 8.1 meters with an LOA of 100 meters that can enter and leave the shipping lane. The depth of the waters in front of the pier of Tanjung Ringgit Port, Palopo City is 7 meters. There is a water area for the activities of the main facilities for port services, namely, Swivel Pool, Ship to Ship Area, and Freight Ship Anchoring Area. And there are water areas for port service supporting facilities activities, namely, Dead Ship Area, Sea Trial Area, Emergency Area, Reserve Area. Keywords: Area; Shipping Line